Morphological and maturity profile of young soccer goalkeepers with 11-14 years of age - Rebelo Goncalves, R.; Severino, V.; Gil, N.; Coelho e Silva, M. J.; Figueiredo, A. J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Studies regarding young soccer players have been increasing in the last decade. However, studies that associate age-group and field position are missing, particularly the characterization of young soccer goalkeepers. Regarding this limitation the purpose of this study is to define the morphological and maturational profile of young soccer goalkeepers according to their age-groups. The sample consisted of 17 male soccer goalkeepers included in two age groups: 11-12 (n=8) and 13-14 (n=9) years-old. For morphological profile were included the following variables: height, weight, arm span, body mass index (BMI), bicristal/biacromial ratio, sitting height/height ratio, adiposity (sum of four skinfolds - tricips, subscapular, suprailiac and calf). Somatotype (Carter & Heath, 1990) was calculated. Maturation was assessed through somatic indicators such as maturity offset (Mirwald et al., 2002) and percentage of predicted adult height (%PAH - Khamis & Roche, 1994). In sequence by age-group, 11-12 and 13-14 years old, respectively, the following trends were noted: Chronological age (12.0, 14.2) height (147.9, 166.9); weight (42.9, 59.8); arm spam (147.5, 171.5); BMI (19.43, 21.24); bicristal/biacromial ratio (72.8, 73.1); sitting height/height ratio (51.0, 50.6) and adiposity (42.0, 33.4). In both somatotypes mesomorphism is the most representative category (3.4-4.7-2.9, 2.3-4.4-3.3). However the 11-12 years-old group has a higher value for endomorphism and the 13-14 age-group a higher value for ectomorphism. Looking at the mean values for the maturational indicators, the maturity offset (-2.02, 0.15) shows that the 13-14 years-old players have already cross the peak height velocity, being this difference in the maturity process corroborated by the %PAH (84.9, 91.6). Malina et al., 2004 found similar results for height and weight in young soccer players for different field positions (defense, midfield and forward). This suggests that, at these ages, the morphological profile of young soccer goalkeeper is not different from that shown by other players in different positions. However more studies regarding the characterization of young soccer goalkeepers using a more extensive pool of variables are needed. Carter JEL, Heath BH (1990). Somatotyping: Development and Applications. Cambridge University Press Mirwald, R.L., Baxter-Jones, A.D.G., Bailey, D.A., & Beunen, G.P. (2002). An assessment of maturity from anthropometric measurements. Medicine and Science in Sports and Exercise, 34 (4), 689-694. Khamis, H.J., Roche, A.F. (1994). Predicting adult stature without using skeletal age: the Khamis-Roche method. Pediatrics, 94(4), 504-507. Malina, R.M., Eisenmann, J.C., Cumming, S.P., Ribeiro, B., & Aroso, J. (2004). Maturity-associated variation in the growth and functional capacities of youth football (soccer) players 13-15 years. European Journal of Applied Physiology, 91, 555-562.